A note on the loop formula for the fermionic determinant - Seiler, Erhard; Stamatescu, Ion-Olimpiu (Journal of physics. A, Mathematical and theoretical, 2016)
A formula expressing the fermionic determinant as an infinite product of smaller determinants is derived and discussed. These smaller determinants are of a fixed size, independent of the size of the lattice and are indexed by loops of increasing length.
Gesehen am 27.05.2020